Analysis of the Effectiveness of Component Maintenance on PT.XYZ Water Pump Machines through the Life Cycle Cost (LCC) Approach - Zidane Albany; Joumil Aidil Saifuddin (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Machine maintenance is an important factor in supporting a manufacturing process that is competitive in the market. Therefore, every company must carry out regular machine maintenance to ensure the machine operates optimally. The aim of this research is to identify damage that may occur to the pump engine and analyze pump maintenance costs which include the cost of repairing or replacing components. The method used in this research is the Life Cycle Cost (LCC) method. The research results show that the maintenance interval for each Bearing component is 1044 hours, Shaft 64 hours, Impeller 76 hours, Gasket 91 hours, Rotor 103 hours, and Bearing Housing 110 hours. The optimal total cost usage at the age of 3 years is IDR. 3,129,542,106/year with the optimal number of mechanics, namely 3 people, previously there were 5 people.